2013
DOI: 10.1111/bph.12334
|View full text |Cite
|
Sign up to set email alerts
|

UDP induces intestinal epithelial migration via the P2Y6 receptor

Abstract: BACKGROUND AND PURPOSEExtracellular nucleotides are released at high concentrations from damaged cells and function through P2 receptor activation. Intestinal epithelial restitution, which is defined as cell migration independent of cell proliferation, is an important initial step in the process of wound healing. In this study, we investigated the role of extracellular nucleotides in intestinal epithelial migratory responses. EXPERIMENTAL APPROACHWound-healing and trans-well migration assays were performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…We noted also the expression of P2Y 1 , P2Y 2 , P2X2, P2X4, and of the adenosine receptor A 2A in IEC. Previous studies also showed the presence of P2Y 6 in Caco2/15 and IEC-6, which are human and rat intestinal cell lines, respectively ( Grbic et al, 2008 ; Nakamura et al, 2013 ).…”
Section: Discussionmentioning
confidence: 78%
“…We noted also the expression of P2Y 1 , P2Y 2 , P2X2, P2X4, and of the adenosine receptor A 2A in IEC. Previous studies also showed the presence of P2Y 6 in Caco2/15 and IEC-6, which are human and rat intestinal cell lines, respectively ( Grbic et al, 2008 ; Nakamura et al, 2013 ).…”
Section: Discussionmentioning
confidence: 78%
“…Among those three receptors, activation of P2Y6 seemed be the most probable because UDPβS was previously shown to be a specific agonist for P2Y6 receptors with no effect on P2Y2 and P2Y4 [20]. Besides, it was shown that UDP induced intestinal epithelial migration via the P2Y6 receptor [17]. Thus, we examined next whether the enhancement of HeLa migration by TMPS and UMPS was specifically mediated via the P2Y6 receptor using knockdown by siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we further examined if tested compounds regulated the migratory potency of these cells with scratch wound migration assay. Recent data suggest that UDP plays a key role in promoting the migration of intestinal epithelium via activation of P2Y6 receptors [17]. [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter are further divided into the ligand-gated ion channel P2X receptors and G-protein-coupled receptors (GPCRs) P2Y, which are subdivided into eight subtypes (P2Y1, 2, 4, 6 and P2Y11–14). P2Y6 receptors, one member of P2Y receptors highly activated by UTP and UDP, mediate various human physiological and pathological processes 8 13 . Over recent years, nucleotides and purinergic receptors have been the focus of increasing attention by immunologists and oncologists since ATP and UTP are found to modulate tumor growth in various tumor models 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%